PERFORMANCE OPTIMIZATION TECHNIQUES IN DATABASE RELIABILITY ENGINEERING - Shekhar Mishra (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Database Reliability Engineering has evolved significantly in response to the growing complexity of enterprise data management systems. This article examines the transformative impact of modern optimization techniques, focusing on indexing strategies, caching architectures, and machine learning integration in database performance management. The article explores how automated tuning solutions and real-time monitoring systems have revolutionized database optimization, particularly in multi-tenant environments. Through analysis of contemporary best practices and implementation methodologies, this article demonstrates the effectiveness of systematic performance testing, validation frameworks, and documentation strategies in enhancing operational efficiency. The article highlights the crucial role of machine learning in predictive optimization and the importance of comprehensive testing protocols in maintaining system stability and performance.